SISTEM INFORMASI PENJUALAN PADA TOKO JILBAB RJS KABUPATEN SUMBAWA BERBASIS WEB - Eri Sasmita Susanto; Yana Karisma; Susi Isnaeni (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
Hijab Shop RJS Sumbawa District that is engaged in the sale of hijab and Muslim fashion has enough customers because the price of the product sold is quite varied, hence it takes a sales information system to help Customers purchase and receive product information from the store. This web-based sales information system aims to help customers or consumers of RJS hijab shop can make purchases and know product information online without having to go to the store directly. The research aims to build a sales information system on the RJS Hijab shop based on the web. The system was developed using the PHP programming language using MySQL as a database. The software development method uses the Waterfalll method. Software testing conducted through black-box testing, the data collection techniques on the study using observations, interviews, documentation and library studies. The final result is a Web-based sales information system used by RJS Hijab shop in Sumbawa district. This system is able to provide product promotion, product sales with bank payments